2018
DOI: 10.1159/000494781
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Dietary Monosodium Glutamate Developmental Neurotoxicity in Rats: A Reappraisal

Abstract: In 1979, we tested dietary monosodium glutamate (MSG) for developmental neurotoxicity in rats. The study was recently cited for establishing a No Observable Adverse Effect Level (NOAEL) for MSG as a food additive resulting in a change in the acceptable daily intake (ADI). Therefore, I re-evaluated the study [Vorhees et al.: Toxicol Appl Pharmacol 1979; 50: 267–282]. Sprague-Dawley rats were fed diets containing 0, 1.7, 3.4, or 5.1% MSG prior to conception, throughout gestation and lactation, and the same diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…According to Glendon, et al, (2016) elaborated that the negative and the positive attitudes related to job can contribute to different business attitudes. It has been found that there is high level of job satisfaction among the employees when they work in a team (Vorhees, 2018). Team with high performance also achieves high level of productivity and higher level of job satisfaction among the employees (Nazim, & Mahmood, 2018).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…According to Glendon, et al, (2016) elaborated that the negative and the positive attitudes related to job can contribute to different business attitudes. It has been found that there is high level of job satisfaction among the employees when they work in a team (Vorhees, 2018). Team with high performance also achieves high level of productivity and higher level of job satisfaction among the employees (Nazim, & Mahmood, 2018).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Even the cumulation of MSG will not be neurotoxic. However, what needs to be considered, when we use MSG, we will not fulfill some micronutrient substances that can be obtained from herbs such as onions, garlic, chili, and other types of herbs [36].…”
Section: Resultsmentioning
confidence: 99%
“…As the main component of food additives, 1 , 2 monosodium glutamate (MSG) was first discovered by Japanese chemist Ju Miao Ikeda. 3 Its main ingredient is L-glutamate sodium salt.…”
Section: Introductionmentioning
confidence: 99%